Rancang Bangun Aplikasi Sarana Prasarana Institut Asia Malang - Andini, Titania Dwi; Subekti, Puji; Islamiyah, Mufidatul (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2021)
Institut Asia Malang has several systems can support the operation of teaching and learning activities, including the infrastructure system. This system needs developed in addition to being an institutional requirement in organizing and administering infrastructure advice, but also a supporting assessment when BAN (National Accreditation Board) conducts an assessment. This assessment is very influential so it is hoped that with more points, the community's credibility to the Asia Institute of Malang will increase.. The method used to build an information system is the Waterfall method. It has 5 phases: Communication, Planning, Modeling, Construction and Deployment. This method is used in building the Information System for Facilities and Infrastructure of Asia Malang (SISAPRA) because it is, sequential in building software. This research also uses 7 stages. The SISAPRA can be accessed via the Web or mobile. The layout are responsive for both types of gadgets often used by userswe wish that this application can assist in managing administration and knowing the status and physical condition.